2016
DOI: 10.1177/1558944716643276
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Approach and Anesthetic Modality for Carpal Tunnel Release

Abstract: Background: Carpal tunnel release (CTR) is commonly performed for carpal tunnel syndrome once conservative treatment has failed. Operative technique and anesthetic modality vary by surgeon preference and patient factors. However, CTR practices and anesthetic trends have, to date, not been described on a nationwide scale in the United States. Methods: The PearlDiver Patient Records Database was used to search Current Procedural Terminology codes for elective CTR from 2007 to 2011. Anesthetic modality (eg, gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…OCTR and ECTR techniques have been described as both safe and effective with equivalent results in the short-term, 47 although ECTR may be costlier. 8,9 With regard to anesthetic type, performing CTR under local anesthetic without sedation has been shown to be effective, 1014 while other anesthetic methods including Bier block, monitored anesthesia care (MAC), or general anesthesia are also well-established options.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…OCTR and ECTR techniques have been described as both safe and effective with equivalent results in the short-term, 47 although ECTR may be costlier. 8,9 With regard to anesthetic type, performing CTR under local anesthetic without sedation has been shown to be effective, 1014 while other anesthetic methods including Bier block, monitored anesthesia care (MAC), or general anesthesia are also well-established options.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study utilizing payment data from United Health Group insurance records concluded that OCTR performed under local anesthetic was less costly than other methods of CTR. 9 However, surgical setting (OR versus PR) was not included as a study variable. 9…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that endoscopic surgery was, on average, $794 more expensive than open surgery. [ 7 ] In The American Academy of Orthopedic Surgery (AAOS) guidelines, it was reported that endoscopic techniques have limited short-term benefits compared to open techniques. [ 8 ]…”
Section: Discussionmentioning
confidence: 99%
“…Turkish surgeons were less likely to prefer WALANT because there is no local procedure room in many clinics and an anesthesiologist is often present in the general operating room. Foster et al[ 7 ] reported that general or regional anesthesia cost $654 more than local anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Anesthesia and surgical techniques may vary according to surgeon preferences and patient-related factors (3). Despite the increasing popularity of local anesthetic methods, general and regional anesthesia techniques are still widely used (4). While elderly patients prefer local methods, younger patients often prefer general anesthesia (5).…”
Section: Introductionmentioning
confidence: 99%